2020
DOI: 10.1093/sleep/zsaa119
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence rates and correlates of insomnia disorder in post-9/11 veterans enrolling in VA healthcare

Abstract: Abstract Study Objectives Post-9/11 veterans are particularly vulnerable to insomnia disorder. Having accurate prevalence rates of insomnia disorder in this relatively young, diverse population, is vital to determine the resources needed to identify and treat insomnia disorder. However, there are no accurate prevalence rates for insomnia disorder in post-9/11 veterans enrolling in the VA Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…A cross sectional study also reported that of those military personnel who returned from deployment with sleep disturbances, 88.2% were identified to suffer from a clinically significant sleep disorder, with 63.6% meeting the diagnostic criteria for insomnia [ 91 ]. Insomnia disorder was also noted in 57.2% of post-9/11 veterans in another study [ 92 ]. Hughes et al .…”
Section: Dementia and Sleepmentioning
confidence: 86%
“…A cross sectional study also reported that of those military personnel who returned from deployment with sleep disturbances, 88.2% were identified to suffer from a clinically significant sleep disorder, with 63.6% meeting the diagnostic criteria for insomnia [ 91 ]. Insomnia disorder was also noted in 57.2% of post-9/11 veterans in another study [ 92 ]. Hughes et al .…”
Section: Dementia and Sleepmentioning
confidence: 86%
“…Thus, the increasing trend in annual prevalence of insomnia diagnoses observed by Alexander and colleagues was also observed in the current study. Despite the relative increases in insomnia diagnoses documented in medical records over time, there remains a notable discrepancy between estimates of insomnia derived from medical records (1.5-3.4% [6,7]) and those derived from epidemiology studies based on interviews and/or surveys (22-57% [9,22]). In both the current analysis and that of Alexander et al, relatively conservative criteria were used to define an insomnia diagnosis (i.e., ≥2 ICD codes occurring greater than 30 days apart but within 390 and 365 days, respectively).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, administrative studies of VA electronic health records (EHR) estimate insomnia prevalence rates from 0.2% to 3.5% [6,7]. Though a 650% relative increase in the age-adjusted prevalence of insomnia was observed in veterans utilizing VA services between fiscal years 2000 and 2010 (from 0.2% to 1.5% [6]), there remains a notable discrepancy between reports of clinically significant insomnia symptoms [9] and expected diagnoses of insomnia in the medical record (7.4-11.8%; [7,10,11]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After additional adjustment for several mental health and medical comorbidities, insomnia remained positively associated with SA. Similarly, Colvonen et al (2020) found that post-9/11 US veterans (N = 5552) enrolling in care at a VHA who reported SI also had high rates (87.7%) of probable insomnia disorder.…”
mentioning
confidence: 88%